Precificação de ativos no mercado de capitais brasileiro: aplicação do modelo de cinco fatores de Fama e French em períodos de crise - Moreira, Kleverson Dáliton Silva (2018)
The capital market is an important catalyst for the development of a country, since it allows the productive allocation of resources, through remuneration to the applicators and the use of the values involved by the companies in productive activities, without the need of an intermediary. Thus, it is necessary to understand how the stock prices are formed. To this end, according to the studies on Efficient Market Hypothesis, initiated in 1970 by Fama, for the strong form of efficiency, investors must pay attention to all the news available, being the historical returns, data provided by reports, as well as those from the economic scenario. Also according to this approach, recent studies show that structural breaks in the economy, whether these locations or even internationally, lead to the change in the relations of risk factors related to the return of stocks over time. In this way, this study aims to apply the established Fama-French Five Factors Model, as well as a modified model by including the variables liquidity and growth opportunities, in order to verify its applicability to the Brazilian market and to understand how moments of economic instability affect the relationship verified to predict the return of shares. For this, a sample was analyzed referring to all the companies listed on the BM&FBOVESPA in the period between 2006 and 2017. Then, regressions with panel data were made separating the data in general period, international pre-crisis, international crisis, post-crise and national recession. The results showed that both models presented variables with explanatory power in relation to stock returns, mainly the seven factors model, especially with the inclusion of the variable growth opportunities. In addition, it was also verified that the different macroeconomic periods changed the relationships verified, being that in periods of crisis it is possible to see the evasion of foreign investors from the national market and the risk aversion by the investors is noticed, there was a higher return on securities of larger companies, higher profitability and greater growth opportunities, as well as for those with a more conservative profile, identified by the variable level of investments.